Millennials definition of luxury and possible implications in the tourism industry: the portuguese case - Silva, Mariana Alexandre Gomes (2021)
This study evaluates how Portuguese Millennials perceive luxury in general terms and regard to the tourism industry. The findings of an interpretive study show that Millennials have two perspectives regarding luxury –a traditional and an unconventional view. These results led to the creation of two models for both luxury in general and luxury in the tourism sector. Each model includes the two perspectives identified and the trends that were considered relevant for each type of profile. The unconventional perception revealed to be more popular among this generation. Regarding the overall luxury, younger Millennials showed amore alternative view of the concept. As for the concrete case of tourism, no conclusions were taken in terms of respondents’ demographics. However, it was possible to find a significant incoherence in terms of participants' definition of luxury in this sector and how they find luxury in their personal touristic experiences.